ANALISIS LAPORAN KEUANGAN SEBAGAI ALAT UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN PADA PT. BUKIT ASAM (PERSERO) TBK TANJUNG ENIM - Anton Trianto (Universitas Indo Global Mandiri)
This study aims to analyze the financial performance of PT. Bukit Asam (Persero) Tbk Tanjung Enim in year of 2014, 2015 and 2016. The analysis tools used in this study are the liquidity ratios (current ratio and quick ratio), the solvency ratios (total debt to assets ratio and total debt to equity ratio), and profitability ratios (return on invesment and return on equity). The results of current ratio and quick ratio research in 2014 shows the company's financial condition is quite good, because the ratios are above the industry average. While in 2015 and 2016 shows the company's financial condition is not good because the ratios are below the industry average. Quick ratios in 2015 and 2016 indicate the company's financial condition is not good, because the ratios are below the industry average. Based on the measuring of solvency ratios, the increase in total debt to assets ratio and total debt equity ratio in 2014-2016 shows that the financial condition is not in the good shape, because the ratios are above the industry average. Judging from the profitability ratio, the decline in return on assets and return on equity in 2016 shows the company's financial performance is not good because the ratios are not maximized in generating profits.Keywords: Liquidity Ratio, Solvency Ratio, and Profitability Ratio